CHOROIDAL BLOOD VESSELS IN RETINAL PIGMENT EPITHELIAL ATROPHY USING OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue Volume 13:Issues 1(2019) (2019) - Maruko, Ichiro; Koizumi, Hideki; Sawaguchi, Shota; Hasegawa, Taiji; Arakawa, Hisaya; Iida, Tomohiro
Abstract : Purpose: To observe choroidal blood vessels in cases sharply demarcated with retinal pigment epithelium (RPE) atrophy at the macular area using en-face optical coherence tomography angiography (OCTA) and standard en-face optical coherence tomography (OCT). Methods: The retrospective study included 12 eyes (8 patients; 5 men, 3 women; average age, 64.3 years) with RPE atrophy seen by ophthalmoscopy. The macular areas with normal and atrophic RPE sections were examined using en-face OCTA with an 840-nm light source (RTVue XR Avanti; Optovue Inc), which system can obtain standard en-face OCT images at identical areas. Images on en-face OCTA and standard en-face OCT were compared with each other when the segmentation range was being set as the full thickness of the choroid by the attached software. Results: Choroidal blood vessels were seen as black on standard en-face OCT images in all cases. However, the choroidal vessels on OCTA were depicted as white in the RPE atrophic area and black in the normal areas. Conclusion: Choroidal blood vessels in the normal sections of RPE were visualized in black on standard en-face OCT and OCTA with an 840-nm light source; however, those in the atrophic parts were observed as white, or with bloodstream, on OCTA images. Choroidal blood vessels cannot be evaluated accurately in commercially available OCTA systems because of blockage of light by the RPE. Abstract : This study retrospectively evaluates the choroidal vessels at the area of retinal pigment epithelium atrophy using en-face optical coherence tomography angiography currently available to set the analysis range to the full thickness of the choroid. Choroidal vessels appear black in the normal area and white in the atrophic areas where light is not blocked by the retinal pigment epithelium. These findings about the choroids should be kept in mind during the clinical usage of the current device.